impact of transformational leadership on organizational citizenship behavior: The role of identification , Work engagement, psychological empowerment and Proactive personality - Marziyeh Dehghanizadeh; Ali Shojaeifard; Sajjad Zarei Pizadani (مطالعات مدیریت بهبود و تحول, 2023)
The purpose of current research is to investigate effect of transformational leadership on organizational citizenship behavior: the role of identification, Work engagement, psychological empowerment and Proactive personality. The statistical population of this research is employees of Agricultural Jihad Organization of Isfahan Province, that With Cochran's formula, a sample of 162 people was selected. research method is descriptive -survey, and the tool for collecting information is the use of the standard questionnaires. Its validity was checked based on factor of confirmatory analysis and its reliability was checked by Cronbach's alpha method and composite reliability. results of the current research show that transformational leadership has a positive and significant effect on organizational identification, Work engagement, and psychological empowerment, therefore, although transformational leadership does not directly have a significant effect on organizational citizenship behavior; However, with the existence of mediating variables of organizational identification, Work engagement and psychological empowerment, this effect becomes significant. Also, the effect of organizational identification, Work engagement and psychological empowerment on organizational citizenship behavior have positive and significant, and proactive personality plays a role in the relationship between transformational leadership on Work engagement and organizational identification and It acts as a moderator and cause of strengthens these two relationshipsIntroduction  Today, the key to the success of organizations is the creation and development of organizational citizenship behavior among employees. The concept of organizational citizenship behavior in the field of organizational behavior emerged two decades ago and continues to develop. This issue is critical and essential for service organizations, such as the Agricultural Jahad Organization, whose activities depend highly on human resources (Sartika et al., 2020). Organizational citizenship behavior is a preferred extra-role and extra-task behavior of employees that promotes the success of organizations (Gammoh et al., 2021). Therefore, considering the importance of organizational citizenship behavior, it is necessary to conduct more research on the mechanisms that influence it; Therefore, the current research has addressed the issue of whether the relationship between transformational leadership and organizational citizenship behavior may be mediated by the concepts of organizational identification, work engagement and psychological empowerment of the employees of the Isfahan Agricultural Jahad Organization and also whether the proactive personality of the employees of the Agricultural Jahad of Isfahan strengthens the effects of transformational leadership on organizational identification and work engagement or not?Materials and MethodsThe statistical population of this research is employees of the Agricultural Jahad Organization of Isfahan Province (280 people). With Cochran's formula, a sample of 162 people was selected. The research method is a descriptive -survey, and the tool for collecting information is standard questionnaires. The data gathering tools in this research are the transformational leadership standard questionnaire of Afsar et al. (2019), the organizational identification standard questionnaire by Su & Swanson (2019), the work engagement standard questionnaire by Schaufeli & Bakker (2004), the employee psychological empowerment's standard questionnaire of Spreitzer (1995); proactive personality's standard questionnaire of Akgunduz et al. (2018); and organizational citizenship behavior's standard questionnaire of Organ (1988). In order to check the validity of the questionnaires, in addition to the content validity, which management professors and experts confirmed, the validity of the questionnaires was also checked from the index of factor loadings. The reliability of the questionnaires was calculated using the two methods of Cronbach's alpha coefficient and composite reliability and confirmed the reliability of the validity of the research instrument. Discussion and ResultsThe findings of the current research show that transformational leadership has a positive and significant effect on organizational identification, work engagement, and psychological empowerment; therefore, although transformational leadership does not directly have a significant effect on organizational citizenship behavior; however, the existence of mediating variables of organizational identification, work engagement, and psychological empowerment, this effect becomes significant. Also, the effect of organizational identification, work engagement, and psychological empowerment on organizational citizenship behavior has positive and significant, and proactive personality plays a role in the relationship between transformational leadership on work engagement and organizational identification. It acts as a moderator and causes of strengthens these two relationships.ConclusionsAccording to the results of this research, it was found that by using the social identity theory, social exchange theory and self-concept theory, the transformational leadership style in the organization increased the employees' perception of the organizational identity and made them feel more attached to their jobs and also the power distance decreased and felt more empowered in his self-concept, and thus these cases increased organizational citizenship behaviors in the employees of the Agricultural Jahad Organization of Isfahan; Therefore, according to the dynamics of the environment, the managers of the agricultural jahad organization should pay attention to the transformational leadership style as one of the best management styles that create and manage changes in the organization and try to manage their employees with this leadership style, and value the development and participation of employees in organizational decision-making and encourage creativity and acceptance of challenges as part of their work so that a sense of purpose is created in people and developed beyond the standards, and as a result, employees also, transfer their ideas and insight to other members.